Analisis Implementasi Pembiasaan dalam Penguatan Profil Pelajar Pancasila: Studi Perbandingan Sekolah Penggerak dan Non-Penggerak - Lola Raudatussolehah; Khairun Nisa; Gozin Najah Rusyada (Mataram University, 2026)
Habit-forming activities are one of the ways schools strive to strengthen the Pancasila Student Profile by instilling character values in students’ daily lives. This study aims to describe the implementation of habit-forming activities in strengthening the Pancasila Student Profile in the dimensions of faith, piety toward God Almighty, and noble character, as well as the dimension of mutual cooperation, and to identify supporting factors, constraints, and efforts made in their implementation at schools that have participated in the School Movement Program and non-participating schools. This study employs a qualitative approach using a comparative study design. The research was conducted at SDN 32 Cakranegara and SDN 40 Cakranegara. The research subjects consisted of school principals, teachers, and students. Data collection techniques included observation, interviews, and documentation, while data analysis utilized the Miles and Huberman model, which encompasses data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that both schools have routinely implemented habit-forming activities through school culture and the learning process to strengthen the dimensions of faith, piety toward God Almighty, and noble character, as well as the dimension of mutual cooperation. SDN 32 Cakranegara has a more diverse and structured habit-forming program, while SDN 40 Cakranegara places greater emphasis on the consistency of implementing these habit-forming activities. Supporting factors include the principal’s commitment, teachers’ active involvement, a positive school culture, and support from the school community. Challenges faced include differences in students’ personalities, a lack of consistency in implementing habit-forming activities, and suboptimal family support. Efforts undertaken include setting a good example, providing ongoing guidance and supervision, offering motivation, and fostering cooperation with parents.